Psychosomatic Status, Personality Traits, and Coping Styles of Bereaved and Non-Bereaved Survivors of the 2008 Wenchuan Earthquake, China - Xiang, Yan-hui; Chi, Xinli; Jiang, Yi-qi; Wang, Rui-fang; Mo, Lei (Frontiers in Psychiatry, 2016)
Objectives: This study examined personality, coping styles, and psychosomatic characteristics and their relationships in bereaved and non-bereaved earthquake survivors. Study design: Cross-sectional survey Methods: A survey was conducted with a sample of 102 non-bereaved survivors and 79 bereaved survivors from Mianyang, Anyang, and similar districts 2 weeks after Wenchuan earthquake. Survivors completed questionnaires including items about demographics, personality characteristics, coping styles, and psychosomatic status. Results: Bereaved survivors had lower scores for gregariousness, trust, and optimism, but higher scores for depressed mood, loneliness, becoming easily fearful, irritation, and anxiety than non-bereaved survivors. In addition, bereaved participants scored higher for avoiding problems, self-blame, and fantasy coping styles than non-bereaved ones. Personality and coping styles significantly correlated with psychosomatic status in bereaved and non-bereaved survivors. Optimism and openness to feelings personality characteristics, and self-blame, avoiding problems, and rationalization coping styles significantly predicted psychosomatic status of bereaved survivors, while openness to fantasy, optimism, order, and trust personality characteristics, and self-blame and avoiding problems coping styles significantly predicted psychosomatic status of non-bereaved survivors. Conclusion: Earthquake survivors experienced PTSD symptoms and negative emotions. Bereaved survivors experienced more serious PTSD symptoms and negative emotions relative to non-bereaved survivors. Appropriate psychological crisis interventions should be conducted for earthquake survivors, especially bereaved survivors.